The experimental research on the propagation laws of cracks in roadway surrounding rock subjected to static-dynamic load - Guo Dongming; Yan Pengyang; Xue Lei; Luo Lang; Yang Jun (矿业科学学报, 2016)
In order to study the propagation law of the crack in surrounding rock subjected to static-dynamic load, the poly methyl methacrylate (PMMA) are used to make specimens containing a single prefabricated crack and dynamic caustics experimental system with explosion load is used to conduct experimental research on the propagation laws of crack in roadway surrounding rock.Study has showed that there exists close relation among the extension displacement of the prefabricated crack, the damage degree of the specimen and confined pressure around the specimen.There is a negative correlation relationship between the extension displacement and the damage degree, which is closely associated with the confined pressure, presenting a rule of increasing firstly and decreasing later as the increasing of confined pressure.Changing the confined pressure around the specimen and keeping the explosion condition unchanged in the study, the prefabricated cracks all appear the phenomenon of alternative variation between extension and arresting, but the value of extension displacement reaches a maximum of 30.84 mm and a minimum of 10.98 mm when the value of confined pressure is 0 MPa and 0.4 MPa respectively, presenting a trend of decreasing firstly and increasing later as the increasing of confined pressure.There exists a close relation between energy release rate around the crack tip and propagation speed of the crack.When energy release rate increases, the propagation speed will increase then, but when the propagation speed decreases, energy accumulation occurs around the tip induced by the explosion stress wave, resulting in energy release rate increasing.